2008
DOI: 10.1029/2007jd009486
|View full text |Cite
|
Sign up to set email alerts
|

A Multisensor satellite‐based assessment of biomass burning aerosol radiative impact over Amazonia

Abstract: [1] Using spatially and temporally collocated multispectral, multiangle and broadband data sets from the Terra satellite, the role of biomass burning (BB) smoke particles on cloud-free top of atmosphere (TOA) direct shortwave aerosol radiative forcing (SWARF) is examined. A 5-year analysis during the peak biomass burning months of August and September is presented over South America (0°-20°S and 45°W-65°W). Our results indicate that over 5 years, the TOA diurnally averaged SWARF (DSWARF) from the Clouds and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 52 publications
2
46
0
2
Order By: Relevance
“…During the past decades, a series of studies on aerosol optical properties and associated direct radiative effects continue to emerge over Amazonia [3,17], Southeast Asia [18,19], Northeast India [11,20,[23][24][25][26][27][28][29], Central India [12], and global land [2,[30][31][32][33] and ocean [4,5,21]. The results showed that the averaged ADRE at TOA was negative at global scale [4][5][6], but it varied regionally probably due to the comprehensive effects of aerosol optical properties and underlying surface characteristics.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…During the past decades, a series of studies on aerosol optical properties and associated direct radiative effects continue to emerge over Amazonia [3,17], Southeast Asia [18,19], Northeast India [11,20,[23][24][25][26][27][28][29], Central India [12], and global land [2,[30][31][32][33] and ocean [4,5,21]. The results showed that the averaged ADRE at TOA was negative at global scale [4][5][6], but it varied regionally probably due to the comprehensive effects of aerosol optical properties and underlying surface characteristics.…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, the large aerosol loadings (AOD550 > 0.6) over YRD do not (Table 2) are all negative, there are still few positive IADRE values ( Figure 12) over 1 • × 1 • grid cells, probably due to the comprehensive effect of aerosol optical properties and surface reflectivity. Generally, positive IADRE tends to be observed over regions with strong absorbing aerosols and high surface reflectivity [2,3]. Assuming that the aerosol optical properties remain constant over bright surfaces, the aerosol layer appears "darker" than its background.…”
Section: Frequency Distribution Of Temporal Variationmentioning
confidence: 99%
See 3 more Smart Citations